The Mycobiome Frontier – Pre & Post 2020 Status: Integrating Fungal Bioactive Compounds, Probiotics, and Antimicrobial Peptides in Modern Therapeutics and Biotechnology. - Mukesh Chander*; Tejal Padda 1 (International Journal of Fungi, 2026)
The fungal kingdom represents an indispensable resource in modern therapeutics and biotechnology, offering a diverse array of bioactive compounds, probiotics, and antimicrobial peptides (AMPs). Functional fungal polysaccharides (FFPs), such as beta-glucans, chitin, and mannans, are centrally involved in modulating the human gut microbiota, providing novel therapeutic avenues for chronic conditions including diabetes, neurodegenerative disorders, and cancer. These compounds act as prebiotics, nourishing beneficial bacteria and enhancing metabolic parameters such as insulin sensitivity and glucose regulation. Concurrently, fungal probiotics, notably Saccharomyces boulardii and S. cerevisiae, are gaining recognition for their ability to reestablish eubiosis, enhance gut barrier functions, and modulate immune responses through the secretion of signaling molecules like short-chain fatty acids (SCFAs). Unlike bacterial counterparts, fungal probiotics are often inherently resistant to antibiotics, making them uniquely valuable for patients undergoing antimicrobial treatment. Furthermore, fungi produce potent antimicrobial peptides and specialized secondary metabolites that have historically defined the golden era of antibiotics and continue to serve as essential candidates for combating multidrug-resistant pathogens. In the sphere of biotechnology, the integration of fungal processes supports a circular bioeconomy through the high-yield production of industrial enzymes, organic acids, pigments, and sustainable mycelium-based materials. This synthesis of fungal applications, ranging from immunosuppressive drugs like cyclosporine to biofuel production, demonstrates the vast potential for personalizing medicine and promoting environmental sustainability. However, the transition to standard medical practice requires large-scale clinical trials to validate safety and efficacy. This review underscores the role of fungi as sustainable biological factories critical for next-generation therapeutic and industrial innovations.
Keywords: Fungal-Gut Biome; Fungal-Probiotics; Keywords: Anticancer; Mushrooms; Yeast peptides